2009
DOI: 10.1007/s12237-009-9229-x
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Estuarine Bacterioplankton, Phytoplankton and Zooplankton to Dissolved Organic Carbon (DOC) and Inorganic Nutrient Additions

Abstract: The response of planktonic bacteria and phytoplankton to various additions of dissolved organic carbon (DOC) as glucose, with and without inorganic nutrients (nitrogen and phosphorus), was tested in the upper to mid Hunter Estuary, Australia. In situ microcosms (1.25 L) were performed at two sites with varying salinities over three seasons. Analysis of variance showed a significant difference among control and treatments for all seasons for the bacterial, dissolved oxygen and chlorophyll a responses (P<0.05). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 51 publications
3
28
0
Order By: Relevance
“…Responses of subsequent trophic levels are thus expected, as has been suggested by other studies showing that increases in nutrient availability evoke a reaction from organisms suspended in the water column, thereby influencing carbon flux in this part of the ecosystem (Olsen et al, 2007). Depending on the level of nutrients, the addition of DOC into the environment stimulates planktonic bacteria or phytoplankton and thus alters the response of zooplankton (Hitchcock et al, 2010). Limited attempts have been made to relate the zooplankton community to the organic matter content in lakes along a trophic gradient.…”
Section: Introductionmentioning
confidence: 58%
See 1 more Smart Citation
“…Responses of subsequent trophic levels are thus expected, as has been suggested by other studies showing that increases in nutrient availability evoke a reaction from organisms suspended in the water column, thereby influencing carbon flux in this part of the ecosystem (Olsen et al, 2007). Depending on the level of nutrients, the addition of DOC into the environment stimulates planktonic bacteria or phytoplankton and thus alters the response of zooplankton (Hitchcock et al, 2010). Limited attempts have been made to relate the zooplankton community to the organic matter content in lakes along a trophic gradient.…”
Section: Introductionmentioning
confidence: 58%
“…Dissolved organic carbon is closely correlated with communities and directly or indirectly influences aquatic organisms and their habitats. Numerous studies have demonstrated a positive correlation between bacteria abundance and DOC concentration; DOC constitutes an alternative source of carbon and energy for zooplankton (Azam et al, 1983;Jansson et al, 1999;Chróst and Siuda, 2006;Hitchcock et al, 2010). On the other hand, by affecting water color, increasing concentrations of DOC in lake water may limit the extent of the euphotic zone and primary production rate, even though DOC is subject to partial photodegradation under sunlight (Perez-Fuentetaja et al, 1999;de Lange et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies within Eastern Australian coastal river and estuarine freshwater inflows have measured patterns in bacterial abundance and biomass, and have revealed a common positive correlation between the import of allochthonous DOC and inorganic nutrients and these parameters (Hitchcock et al 2010, Hitchcock & Mitrovic 2013. We have expanded upon these observations by identifying shifts in BCC and taxonomic diversity in response to an inflow event and have related these changes to the input of allochthonous C and inorganic nutrients.…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies have performed nutrient manipulation experiments using microcosms to investigate heterotrophic bacterial growth response to simulated inflows, floods and their associated nutrient inputs (Hitchcock et al 2010, Hitchcock & Mitrovic 2013). These studies have indicated that heterotrophic bacterial growth in rivers and estuaries is often limited or co-limited by available DOC, N and P during periods of low river discharge (Jansson et al 2006, Hadwen et al 2010, Hitchcock et al 2010, Hitchcock & Mitrovic 2013), but very little is known about how these events influence the composition and diversity of bacterial assemblages, or the implications for lotic chemical cycling and trophic dynamics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation